Reorientasi Nilai-nilai Kepemimpinan Lembaga Pendidikan Islam Muhammadiyah di Indonesia - Sadari Sadari; Robiatul Adawiyyah; Nurhidayat Nurhidayat; Ummah Karimah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
Muhammadiyah is a community organization engaged in education and is popular in Indonesia. Muhammadiyah has been successful in the local-Javanese scope, as well as at the national level. Muhammadiyah educational institutions spread throughout the territory of Indonesia. But as it went on it turned out to have an impact on the emergence of two texture models of Muhammadiyah educational institutions related to leadership, namely the effective model and what it is. The first model, the institution is supported by a strong leadership style, while the second is the opposite. The article further analyzes how these two distinctions can emerge and what steps are important to prepare with the initial assumption that reliance on the